The Antifungal Activity of a Polygalacturonic and Caprylic Acid Ointment in an In Vitro, Three-Dimensional Wound Biofilm Model - Bahgat Z. Gerges; Joel Rosenblatt; Y-Lan Truong; Ying Jiang; Issam I. Raad (Journal of Fungi)
Candida colonization and biofilms are significant contributors to impaired wound healing. Consequently, improved treatments are needed to eradicate Candida biofilms in wounds. Wounds present complex biofilm extracellular matrix environments, with microbial cells frequently enmeshed in matrices comprising wound exudate macromolecular gels. We evaluated the ability of a polygalacturonic and caprylic acid (PG + CAP) ointment to eradicate Candida albicans, C. parapsilosis, C. glabrata, C. tropicalis, and C. auris biofilms in a fibrin gel wound biofilm model of the complex wound biofilm environment. Hypochlorous acid (HOCl) is a disinfecting antimicrobial agent that is widely used as wound irrigant, and this was used as a comparator. A single treatment with PG + CAP reduced the number of viable organisms in the C. albicans and C. glabrata biofilms by over 5 log10, in the C. parapsilosis and C. auris biofilms by over 4 log10, and in the C. tropicalis biofilm by 3.85 log10. PG + CAP was superior (p < 0.01) to HOCl in eradicating all Candida species biofilms, except for C. auris, for which both treatments fully eradicated all viable organisms. The use of HOCl in Candida-colonized wounds should include consideration of the extracellular matrix load in the wound bed. PG + CAP warrants further study in wounds compromised by Candida biofilms.